Severe GABAA receptor encephalitis without seizures: A paediatric case successfully treated with early immunomodulation. (May 2018) - Nikolaus, Marc; Knierim, Ellen; Meisel, Christian; Kreye, Jakob; Prüss, Harald; Schnabel, Dirk; Kallinich, Tilmann
Abstract: Background: Autoimmune-mediated processes are the driving force behind many neurological diseases. Autoimmune encephalitis, a group of syndromes, mediated by or at least associated with autoantibodies against neuronal tissue, have gained increasing importance especially in paediatric neurology. Since the first NMDAR encephalitis was described a growing number of patients with encephalopathy, seizures and psychiatric symptoms were found to suffer from treatable autoimmune disorders. Recently a severe form of encephalitis associated with GABAA R antibodies was described showing extensive MRI abnormalities and refractory seizures. Case: We now describe a child with catatonia and encephalopathy due to antibodies against the GABAA receptor. It is a rare paediatric case without the development of seizures despite severe encephalopathy. Relevance: The report extends the phenotype of this rare disease. It demonstrates a favourable outcome after introduction of an early and aggressive immunomodulatory therapy. Due to the child's history of previous viral meningitis, the case raises questions about the unrevealed mechanisms leading to autoimmune encephalitis, including the model of a viral trigger as discussed in Herpes infection and NMDAR encephalitis. Finally, it describes in detail the neuropsychological symptoms and cognitive functions during disease flare and recovery. Highlights: A paediatric case of GABAA R encephalitis without development of seizures despite severe phenotype. A full recovery upon early immunosuppression unlike previous reports. A report extending the phenotype of this rare disease. A medical history raising questions about the aetiology of autoimmune encephalitis.